Evaluation of Salivary and Serum Total Antioxidant Capacity and Lipid Peroxidation in Postmenopausal Women - Fatemeh Zovari; Hadi Parsian; Ali Bijani; Ameneh Moslemnezhad; Atena Shirzad (Hindawi Limited, 2020)
Objective. In menopause, reduction of estrogen hormone affects oxidative stress process in serum. Oxidative stress in saliva plays a significant role in the pathogenesis of oral diseases. The aim of this study was to investigate the total antioxidant capacity and lipid peroxidation in the serum and saliva of premenopausal and postmenopausal women. Methods. In this case control study, 50 postmenopausal women (case group) and 48 premenopausal women (control group) were selected. The unstimulated whole saliva and serum of the postmenopausal and premenopausal women were collected. The total antioxidant capacity (TAC) of the saliva and serum was measured by ferric reducing antioxidant power (FRAP). Also, malondialdehyde (MDA) was measured by thiobarbituric acid reactive substance (TBARS) method for serum and saliva. Then, the obtained data were analyzed by SPSS 17, whereby Mann-Whitney test and Spearman's correlation test were used. P<0.05 was considered statistically significant. Results. The postmenopausal group had significantly lower mean serum TAC and higher mean serum MDA than the control group (P<0<001 and P<0.01, respectively). The mean salivary TAC and MDA, however, did not differ significantly between the case and control group (P=0.64 and P=0.08, respectively). Conclusion. In postmenopausal women, with elevation of serum MDA and reduction of serum TAC, the extent of serum oxidative stress grows, but MDA and TAC levels of saliva do not change.